Law in the Everyday Lives of Transnational Families: An Introduction - Betty De Hart; Wibo van Rossum; Iris Sportel (Oñati Socio-Legal Series, 2013)
In the introduction of this special issue on “Law in the everyday lives of transnational families”, we argue that in the socio-legal literature on transnationalism and transnational legal process, ordinary people as actors are missing. On the other hand, what is missing from the abundant literature on transnational families, is law, or are ordinary people. In this special issue, we look at how transnational families as legal actors are part of transnational legal processes and how transnational families meet with different types of legal rules that mingle with and influence the personal and private sphere of family life. We specific look at three issues that come up in this context: the power of law, how transnational family members use law and the role of networks and family. En la introducción del número especial sobre “Derecho en el día a día de las familias trasnacionales”, defendemos que en la literatura sociojurídica sobre trasnacionalismo y procesos legales trasnacionales, no se contemplan las personas corrientes como actores. Por otro lado, lo que falta en la abundante literatura sobre familias trasnacionales es el derecho, o son las personas corrientes. En este número especial se analiza cómo las familias trasnacionales, en el papel de actores legales, son parte de procesos legales trasnacionales, y cómo las familias trasnacionales cumplen diferentes tipos de normas legales que atienden a, e influyen en la esfera personal y privada de la vida familiar. Específicamente, se contemplan tres aspectos que surgen en este contexto: el poder del derecho, cómo usan los miembros de las familias trasnacionales el derecho y el papel de las redes de conocidos y el derecho.